Blast of silence [videorecording (Blu-Ray)] - Baron, Allen; Baron, Allen; Salt, Waldo; Stander, Lionel; McCarthy, Molly (Actress); Tucker, Larry, 1934-2001 (Criterion collection, 2023)
Swift, brutal, and blackhearted, Allen Baron's New York City noir film is a sensational surprise. This low-budget, carefully crafted portrait of a hit man on assignment in Manhattan during Christmastime follows its stripped-down narrative with mechanical precision, yet also with an eye and ear for the oddball details of urban living and the imposing beauty of the city. At once visually ragged and artfully composed, and featuring rough, poetic narration performed by Lionel Stander and written by Waldo Salt (both uncredited), it is a stylish triumph.